Case report: isolated pulmonary valve endocarditis in a 39-year-old patient with intravenous drug abuse. Issue 6 (26th November 2020) - Platz, Martin Richard; Stöbe, Stephan; Baum, Paul; Metze, Michael
Abstract: Background : Isolated pulmonary valve endocarditis is a very rare form of right-sided infective endocarditis. Due to the anatomy, in most cases, just the tricuspid valve is involved. Diagnosis can be challenging because of non-specific symptoms (fever, dyspnoea, haemoptysis, and pleuritic chest pain) and difficulty of detection by echocardiography. Risk factors include intravenous drug abuse, congenital heart disorders, alcohol abuse, male sex and central venous catheters, or pacemaker leads. Case summary : A 39-year-old homeless male patient, who was a current intravenous drug user, presented with fever, dyspnoea, and haemoptysis. The chest X-ray showed bilateral infiltrates. Empiric antibiotic treatment was initiated. Blood cultures showed the presence of Streptococcus dysgalactiae . Atypical causes of pneumonia were excluded. Systemic embolism was suspected, and a computed tomography scan of brain, thorax, and abdomen was performed. Multiple septic embolic lesions were detected in both lungs. Echocardiography revealed an isolated pulmonary valve endocarditis. Penicillin G and gentamycin were administered intravenously for a duration of 6 and 2 weeks, respectively. The patient was discharged in stable condition but did not return for outpatient clinical appointments. Discussion : To detect rare causes of right-sided infective endocarditis, repeated echocardiograms with special focus on the pulmonary valve may be required. Usually, antibiotic treatment alone leads to recovery. In special situations (heart failure, septic shock, or large vegetation size) surgery is required. Due to the high risk of postoperative complications, surgery in intravenous drug users should be avoided if possible.